In Situ Encapsulated RhB@Er-MOF with Dual-Emitting Rationmetric Fluorescence for Rapid and Selective Detection of Fe(III) by Dual-Signal Output - Xiaoyan Yao; Xueyi Lv; Dongmei Zhang; Xiangyu Zhao; Kaixuan Zhong; Hanlei Sun; Hongzhi Wang; Licheng Liu; Wentai Wang; Shuo Yao (Chemistry, 2025)
A novel polyhedron-based anionic Er-MOF with three types of cages and abundant open metal sites (OMSs) and Lewis base sites (LBSs) has been successfully synthesized. The inorganic secondary unit possesses a rarely reported six-connected three-nucleated rare-earth cluster, and the overall framework shows a new (3,3,6)-connected topology. The Er-MOF has good fluorescence selectivity and anti-interference performance with Fe3+ and Cu2+. In addition, benefiting from the anionic framework, nanoscale cavity and small window size of the Er-MOF, the composite RhB@Er-MOF has been synthesized by in situ encapsulation of the cationic dye Rhodamine B (RhB). It can provide dual-emitting fluorescence that facilitates self-calibration in sensing. The RhB@Er-MOF has higher accuracy than the Er-MOF with regard to the fluorescence-selective and anti-interference performance of Fe3+ and quenching coefficient Ksv values of 1.97 × 104 M−1, which are attributed to its self-calibration function that can eliminate environmental interference. The fluorescence quenching mechanism was explained by our experiments and density functional theory (DFT) calculations. Furthermore, RhB@Er-MOF can achieve the visual and rapid selective detection of Fe3+ by a smartphone RGB color analysis application, resulting in the dual-signal output performance of the material.